USING VIRTUAL WRITING TUTOR IN TEACHING WRITING TO EFL LEARNERS - Zein, T. Thyrhaya; Sinar, T. Silvana; Deliana, Deliana (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The rapid advancement of technology has reshaped various sectors of human life, including education, where digital tools are increasingly integrated into instructional practices. Among these tools, the Virtual Writing Tutor (VWT) has emerged as a promising platform for enhancing writing instruction through real-time feedback and automated assessment. While existing studies have explored VWT’s potential in assisting writing tasks, limited research has examined its integration into a structured, pedagogically sound writing learning model. This study aims to evaluate the effectiveness of incorporating VWT within a comprehensive writing instruction model and its impact on improving students’ academic writing skills. Employing a descriptive research design, this study involved 30 undergraduate students from the English Literature Study Program at Universitas Sumatera Utara. Writing tests were administered before and after the implementation of the VWT-integrated model. Students’ written outputs were assessed using VWT’s diagnostic features, focusing on coherence, grammar accuracy, vocabulary use, punctuation, and spelling. The data were analyzed descriptively to capture improvement patterns and student performance trends. The findings demonstrate that VWT significantly supports students in the writing process by helping them generate, structure, and refine their ideas with more autonomy. Students also showed improved awareness of language mechanics and vocabulary selection. A novel contribution of this study is its proposal of a VWT-integrated instructional framework that not only facilitates independent learning but also complements teacher feedback. These findings underscore the importance of embedding technological tools like VWT into writing pedagogy to enhance writing outcomes and promote learner-centered instruction in higher education.